Digital Services for Agriculture - Delinthe, Luken; Zwart, Sander J. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Digital services for agriculture across Africa, with a specific focus on Ghana, were inventoried. An online survey, targeting the service providers, was designed and implemented, to map the services that were provided, communciation channels used, products specifically for the irrigation sector, and specific attention from women and youth. The report served to pre-select companies for co-design of an irrigation service.